Rhythmic skills mediate the link between music training and cognition via attention and phonological processing. - Lizcano-Cortés, Fernando; Ripollés, Pablo; Barrios, Fernando A.; Assaneo, M. Florencia (Communications Psychology, 2026)
Rhythmic abilities are linked to performance across a range of cognitive tasks, yet the mechanisms underlying this relationship remain unclear. We evaluated 98 Mexican participants using the Speech-to-Speech Synchronization Test (SSS-Test), a self-report measure of musical training, and an extensive cognitive battery. Analyses revealed that phonological language processing and temporal attention are the core cognitive skills associated with auditory-motor rhythmic proficiency (as assessed by the SSS-Test). Importantly, this relationship appears thresholded: cognitive benefits emerge only when rhythmic abilities exceed a specific level, with further refinements conferring no additional advantage. Moreover, we show that the link between musical training and cognition is fully mediated by this rhythmic performance threshold. These findings provide a unifying framework for understanding how rhythmic skills impact cognition and clarify the mechanisms through which musical training may confer cognitive benefits. Rhythmic ability enhances attention and phonological processing only after surpassing a specific threshold; beyond this point, additional improvements confer no further benefit. This thresholded relationship may explain the positive impact of musical training on cognition.